2014
DOI: 10.1080/13607863.2014.971706
|View full text |Cite
|
Sign up to set email alerts
|

Differences in life satisfaction among older community-dwelling Hispanics and non-Hispanic Whites

Abstract: Objectives Hispanics are the fastest growing ethnic/racial group of the older adult population in the U.S., yet little is known about positive mental health in this group. We examined differences in life satisfaction between demographically-matched groups of older Hispanics and non- Hispanic Whites, and sought to identify specific factors associated with these differences. Methods Participants included 126 community-dwelling English-speaking Hispanics ages 50 and older, and 126 age-, gender-, and education-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 76 publications
3
16
0
Order By: Relevance
“…While adjusting for all covariates in the multivariate analysis, Hispanics had the highest LS despite their disadvantaged socioeconomic status on average. Hispanics with high school or lower levels of education even reported higher levels of LS than their White counterparts, and this is consistent with several previous studies (Calvo, Carr, & Matz-Costa, 2016; Marquine et al, 2015). This finding might be explained in part by the “Hispanic Paradox,” referring to the fact that Hispanic immigrants have lower mortality rates and longer life expectancies than non-Hispanic Whites, despite lower average income and education (Abraido-Lanza, Dohrenwend, Ng-Mak, & Turner, 1999; Hummer & Hayward, 2015; Markides & Coreil, 1986; Markides & Eschbach, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While adjusting for all covariates in the multivariate analysis, Hispanics had the highest LS despite their disadvantaged socioeconomic status on average. Hispanics with high school or lower levels of education even reported higher levels of LS than their White counterparts, and this is consistent with several previous studies (Calvo, Carr, & Matz-Costa, 2016; Marquine et al, 2015). This finding might be explained in part by the “Hispanic Paradox,” referring to the fact that Hispanic immigrants have lower mortality rates and longer life expectancies than non-Hispanic Whites, despite lower average income and education (Abraido-Lanza, Dohrenwend, Ng-Mak, & Turner, 1999; Hummer & Hayward, 2015; Markides & Coreil, 1986; Markides & Eschbach, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Although empirical assessment of factors contributing to the “Hispanic Paradox” is still limited, culture-related factors may be the most relevant ones to consider, as quality of life is a value-laden and culturally dependent construct (Iwasaki, 2007; WHO, 1997). Religious practice and spiritual experiences, for instance, are found to be associated with SWB (Ellison, 1991), and thus may play important roles in explaining the “Hispanic Paradox” in LS (Marquine et al, 2015). In the HRS, about 96% of Hispanics were religious comparing to 92% of Whites and 95% of African Americans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured dispositional optimism using three items (I’m always optimistic about my future; In uncertain times, I usually expect the best; Overall, I expect more good things to happen to me than bad), on a 6 point Likert scale (1=strongly disagree to 6=strongly agree), from the Life Orientation Scale (Cronbach’s alpha= .80, Scheier, Carver, & Bridges, 1994). Marquine et al (2015) validated this scale with Hispanic populations. The average of the three dispositional optimism items created an index of uncertainty avoidance-optimism, ranging from 1 - 6, with a higher number indicating low uncertainty avoidance.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Another study found that Hispanics over age fifty had greater life satisfaction than non-Hispanic whites of the same age. Part of this difference was attributed to higher levels of spirituality among Hispanics [47]. Among Latino immigrant men, life satisfaction was positively associated with familism (familismo), spirituality, work satisfaction, and perceived health, and it was negatively associated with perceived discrimination [48].…”
Section: Satisfaction With Lifementioning
confidence: 99%